Suicide risk remission in collaborative care: a large-scale observational study - Carol Hardy; Virna Little; Brandn Green (Frontiers in Psychiatry)
IntroductionPrimary care settings represent a critical opportunity for suicide prevention, as many individuals who die by suicide visit primary care providers in their final month of life. The Collaborative Care Model (CoCM) offers a structured approach to behavioral health treatment in primary care, but research on its effectiveness for suicide risk management is limited. This study examined how clinical variables (days enrolled, clinical touchpoints, psychiatric consultations) relate to suicide risk outcomes in CoCM, and how these relationships are moderated by initial depression severity.MethodsData from 3,599 patients with suicide risk flags who completed CoCM treatment were analyzed using ordinal logistic regression. Changes in suicide risk level from intake to discharge were categorized as improved, unchanged, or regressed.ResultsLonger enrollment (OR=1.432, p<.001) and more clinical touchpoints (OR=2.584, p<.001) predicted improved outcomes. Higher baseline depression scores predicted poorer outcomes (OR=0.741, p<.001) but showed significant interaction with days enrolled. More psychiatric consultations (OR=0.813, p<.001) were associated with risk regression, likely reflecting appropriate escalation of complex cases.DiscussionCoCM shows promise for suicide risk management in primary care, with sustained engagement and frequent clinical contact improving outcomes. Results suggest treatment intensity should be tailored to initial depression severity.